2018
DOI: 10.1186/s12936-018-2393-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two artemisinin-based combinations for the treatment of malaria in pregnancy in India: a randomized controlled trial

Abstract: BackgroundIn India, the recommended first-line treatment for malaria in the second and third trimester of pregnancy is artesunate + sulfadoxine-pyrimethamine (AS+SP). However, data on safety and efficacy of artemisinin-based combination therapy (ACT) in pregnancy is limited. This study assessed the safety and efficacy of AS+SP and artesunate + mefloquine (AS+MQ) for treatment of Plasmodium falciparum in pregnancy in India.MethodsThis open-label, randomized clinical trial was conducted from October 2010 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Our search identified 30 studies with PCR-corrected efficacy. With the exception of two unpublished studies, individual patient data from 4968 (92%) of 5360 episodes in 19 studies 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were shared and pooled for the analyses of PCR-corrected efficacy ( figure 1 ).
Figure 1 Study selection ACT=artemisinin-based combination therapies.
…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 30 studies with PCR-corrected efficacy. With the exception of two unpublished studies, individual patient data from 4968 (92%) of 5360 episodes in 19 studies 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were shared and pooled for the analyses of PCR-corrected efficacy ( figure 1 ).
Figure 1 Study selection ACT=artemisinin-based combination therapies.
…”
Section: Resultsmentioning
confidence: 99%
“…In India, malaria transmission is relatively low and varies markedly between different ecological settings 7. A study conducted in the eastern state of Jharkhand in 2007 showed that placental parasitaemia, measured by RDT or placental smear microscopy, ranged from 0.8% in urban areas to 3.6% in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…UNESCO encourages research into local medicinal plants with the hope of finding anti-malarial drugs that are more efficient and could combat the artemisinin resistant malaria parasite [ 4 ]. Currently artemisinin-based combination therapy is recommended for treatment of falciparum malaria and its effectiveness against other plasmodial species [ 5 ]. In 1996 among the top 20 prescription dispensed, six were derived from natural products and the clinical use of drugs, such as artemisinin and taxol, further proved that plants are sources of novel drugs entities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%